Fatal Chromobacterium violaceum bacteraemia in rural Bandundu, Democratic Republic of the Congo. (January 2015) - Bottieau, E.; Mukendi, D.; Kalo, J.-R.; Mpanya, A.; Lutumba, P.; Barbé, B.; Chappuis, F.; Lunguya, O.; Boelaert, M.; Jacobs, J.
Abstract: We describe the first case of bacteraemia caused by Chromobacterium violaceum in the Democratic Republic of the Congo. This diagnosis was made in an apparently healthy adult who was admitted to a rural hospital of the province of Bandundu with severe community-acquired sepsis. The patient developed multi-organ failure and died; to our knowledge, this is the first reported fatal case in an adult in Africa.